Exploring A New Frontier in Singapore's Private International Law: IM Skaugen SE v MAN Diesel & Turbo SE [2016] SGHCR 6 - CHNG, Wei Yao, Kenny (Institutional Knowledge at Singapore Management University, 2016)
The establishment of the Singapore International Commercial Court (“SICC”) marks a significant development in Singapore’s private international law. This note leverages on the Singapore High Court decision of IM Skaugen SE v MAN Diesel & Turbo SE [2016] SGHCR 6 to discuss two key issues raised by the SICC: the relationship between the Singapore High Court’s and the SICC’s jurisdictional rules, and the applicable test for the exercise of the SICC’s jurisdiction. This note argues that the possibility of a transfer to the SICC should influence the High Court’s exercise of its international jurisdiction, and that the SICC should not apply the common law jurisdictional approaches for the exercise of its international jurisdiction, but a unique test that recognises the competing policy objectives it has to balance.